Genetic origins of the introduced pea weevil (Bruchus pisorum) population in Ethiopia - Scheepers, Loraine Cornelia (University of the Free State, 2012)
This study aimed to determine the origin of pea weevils (Bruchus pisorum) in Ethiopia and to determine the current population structure across that country. The pea weevil is presently a widely distributed pest of peas in Ethiopia, causing huge financial losses. Conflicting hypotheses exist on the origin of B. pisorum in Ethiopia. It was possibly introduced to Ethiopia sometime in the 1970s, or it might have occurred historically in the area in very low numbers. The methodology of this study consisted of finding populations of pea weevils across the globe and then comparing these populations with the population currently found in Ethiopia. Specimens were obtained from Ethiopia, the USA, Germany and Australia. Gene sequences of pea weevils from China and Japan were also downloaded from GenBank to serve as reference material. DNA was extracted, amplified and sequenced using standard protocols, with the exception of the USA sample which was composed of museum specimens that demanded a non-destructive DNA extraction method. Three gene regions were used in this study: the Elongation Factor 1alpha (EF-1α), Cytochrome oxidase subunit one (COX1) and Cytochrome b (Cytb). The COX1 and Cytb sequence data provided insight into a possible source population of pea weevils in Ethiopia, whereas results from EF-1α were uninformative. Pea weevils from the USA were identified as a possible direct source, but it should be noted that these pea weevils are not endemic to the USA. The possibility of an endemic population of pea weevils in Ethiopia is also discussed. Tests for differentiation indicated that there was some differentiation between the Ethiopian subpopulations. This variation is discussed with reference to possible multiple sources of introduction for the current population in Ethiopia, genetic drift since introduction, and the possibility of a mixture of endemic and introduced genetic material in B. pisorum in Ethiopia.

Die doel van hierdie studie was om die oorsprong van die ertjiekalanders (Bruchus pisorum) in Ethiopië te bepaal en om die huidige populasie struktuur van hierdie insekte te ondersoek. Die ertjiekalander is tans 'n wydverspreide pes van ertjies in Ethiopië wat groot ekonomiese verliese veroorsaak. Botsende hipoteses oor die oorsprong van B. pisourm in Ethiopië bestaan. Die ertjiekalander is moontlik per abuis in die 1970s in Ethiopië ingevoer of alternatiewelik het dit histories in baie lae getalle in die gebied voorgekom. Die metodiek van hierdie studie het bestaan uit die soek na populasies van ertjiekalanders regoor die wêreld, en die vergelyking van hierdie populasies met die huidige Ethiopiese populasie. Eksemplare is verkry vanaf Ethiopië, die VSA, Duitsland en Australië. DNS volgordes van ertjiekalanders in China en Japan is ook vanaf GenBank afgelaai om te dien as verwysingmateriaal. DNS is onttrek, ge-amplifiseer en die DNS volgordes van die gene is bepaal deur die gebruik van standaard protokolle. Die VSA eksemplare was museum eksemplare en het en „n nie-vernietigende DNA onttrekkings metode vereis. Drie gene is in hierdie studie gebruik, naamlik Verlenging Faktor 1alpha (EF-1α), sitochroom oksidasie subeenheid een (COX1) en sitochroom b (Cytb). Die COX1 en Cytb volgorde data het insig in 'n moontlike bron-populasie van ertjiekalanders in Ethiopië verskaf, terwyl die resultate van die EF-1α geen nie insiggewend was nie. Ertjiekalanders van die VSA is as 'n moontlike direkte bron geïdentifiseer, maar dit moet in ag geneem word dat ertjiekalanders nie endemies aan die VSA is nie. Die moontlikheid van 'n endemiese populasie ertjiekalanders in Ethiopië word ook bespreek.Toetse vir differensiasie het aangedui dat daar differensiasie tussen die Ethiopiese subpopulasies bestaan. Hierdie variasie word bespreek met verwysing na die moontlikheid van veelvuldige bronpopulasies vir die huidige Ethiopiese populasie, genetiese drywing sedert invoering en die moontlikheid van 'n mengsel van inheemse en uitheemse genetiese materiaal in B. pisorum in Ethiopië.
Dissertation (M.Sc. (Genetics))--University of the Free State, 2012
Keywords: Pea-weevil -- Ethiopia -- Genetics; Introduced insects -- Ethiopia; Insect pests -- Ethiopia; Insect populations -- Ethiopia; Chrysomelidae